The Influence of CAMEL Ratio on Bank Stock Price Changes Post COVID-19 - Dasuki, Havid; Suripto, Suripto; Wardianto, Kussuyatmono Bagus (Eastasouth Institute, 2025)
The purpose of this study is to empirically test the effect of CAMEL on changes in stock prices after COVID-19 in banking companies listed on the Indonesia Stock Exchange. This study is descriptive explanatory with a quantitative approach. Analysis with data processing using the EViews program. The results of the study indicate that CAR has no significant effect on changes in stock prices, RORA has a significant effect and has a negative relationship direction on changes in stock prices, NPM has no significant effect on changes in stock prices, ROA has a significant effect and has a positive relationship direction on changes in stock prices, and LDR has no significant effect on changes in stock prices.